2018
DOI: 10.3390/w10020228
|View full text |Cite
|
Sign up to set email alerts
|

Low Frequency Waves Detected in a Large Wave Flume under Irregular Waves with Different Grouping Factor and Combination of Regular Waves

Abstract: This paper describes a set of experiments undertaken at Universitat Politècnica de Catalunya in the large wave flume of the Maritime Engineering Laboratory. The purpose of this study is to highlight the effects of wave grouping and long-wave short-wave combinations regimes on low frequency generations. An eigen-value decomposition has been performed to discriminate low frequencies. In particular, measured eigen modes, determined through the spectral analysis, have been compared with calculated modes by means o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Riefolo et al [15] analyzed experimental data from large scale wave flume under the project SUSCO (Swash zone response under grouping Storm Conditions) founded by EC Programme HYDRALAB III. The authors highlighted the effects of wave grouping and long-wave short-wave combination regimes on low frequency wave generations and clarified their influence on morphodynamics.…”
Section: Coastal Morphodynamicmentioning
confidence: 99%
“…Riefolo et al [15] analyzed experimental data from large scale wave flume under the project SUSCO (Swash zone response under grouping Storm Conditions) founded by EC Programme HYDRALAB III. The authors highlighted the effects of wave grouping and long-wave short-wave combination regimes on low frequency wave generations and clarified their influence on morphodynamics.…”
Section: Coastal Morphodynamicmentioning
confidence: 99%
“…In order to analyze the longest standing waves in the flume, the lowest frequencies are determined and compared with those measured. The wave flume natural frequencies are provided by carrying out the eigenvalue analysis, as in details described by Riefolo et al [51,52], where different formulas found in the literature were compared. Here, the frequencies calculated with the formula proposed by Merian [43], by referring to the maximum water depth (2.5 m) in the wave flume, are shown in Table 7.…”
Section: Eigenvaluesmentioning
confidence: 99%
“…Moreover, it is worth noting that the local effect on a beach profile of bichromatic or monochromatic waves can be significantly different due to the interaction of the LFWs that affects the spectra. Considering the typical pattern of modes F 1 -F 4 (according to [45,52]), some differences can be observed in Figure 8. In fact, it is identified:…”
mentioning
confidence: 99%